The Effect of Organizational Culture, Principal Leadership and Motivation on Teacher Performance in Madrasah - Hasibuan, Syahrul (JURNAL AL-TANZIM, 2022)
This study aims to determine whether direct and indirect effects of organizational culture, principal leadership, and motivation on teacher performance at Madrasah Aliyah Irsyadul Islamiyah. The type of research used is a quantitative research using multiple linear regression formulas and flow analysis as its development. This study found that: 1) there was a significant influence between teacher motivation and teacher performance of 0.570. The contribution given by teacher motivation to teacher performance is 31.2%; 2) The influence of organizational culture and principal's leadership on teacher performance is 0.642. The contribution given by the head of madrasa communication to teacher performance is 41.2%; 3) Teacher motivation, organizational culture, and principal leadership together on teacher performance have a strong relationship of 0.737. The contribution of the two independent variables to the teacher's performance at Madrasah Aliyah Irsyadul Islamiyah was 54.3%, while the remaining 45.7% was the contribution of other variables not measured in this study.